Motivasi, Kepuasan dan Produktivitas Kerja Penyuluh Lapangan Peternakan - Aida Vitayala Hubeis (Faculty of Animal Science, Bogor Agricultural University, 2008)
It is well documented that productivity of workers is influenced by both internal and external factors. The objective of this study was to provide insights into motivation, job satisfaction and job productivity of Animal Husbandry Field Extension Workers (FEW). The analysis was carried out using the Spearman rank correlation. The respondents of the study were 36 FEW, in Sukabumi district, West Java. The results of the study showed that most of FEW were male, married, relatively old, and had more than three children. Most of them had a diploma certificate, had been participating in several trainings, had 20 years of working experience, and belong to third rank employee. It was found that all internal factors of FEW (achievement, recognition, job, and responsibility) had a positive correlation with job productivity. On the contrary, there were only two external factors, employment status and personal communication, which had a positive correlation with job productivity of FEW. Other external factors, including administration and policy, supervision, salary and reward, and working condition factors, were negatively correlated with job productivity of FEW. Finally, the findings also reveal evidence that three out of four job satisfactions (psychology, social, and physical condition) were positively correlated with work productivity of FEW whereas financial aspect was not. Key words: extension, motivation, job satisfaction, job productivity